Warburg (HARD +/- E) syndrome without retinal dysplasia: case report and review. Issue 10 (October 1986) - Attia, M F; Burn, J; McCarthy, J H; Purohit, D P; Milligan, D W
Abstract : Warburg syndrome is a recently defined autosomal recessive oculocerebral syndrome. It was previously given the acronym HARD +/- E, indicating what were regarded as the pathognomonic features, namely hydrocephalus, agyria, and retinal dysplasia with or without encephalocele. We report the case of a male infant with the typical cerebral features of hydrocephalus, agyria, and pseudoencephalocele, but without retinal dysplasia. Peters' anomaly and optic nerve hypoplasia were the main ocular defects. We believe that anterior chamber defects and optic nerve hypoplasia are the ocular defects more directly related developmentally to the cerebral defects. Definition of ocular defects is important, since diagnosis and counselling rely heavily on ocular signs, which help to distinguish this syndrome from neural tube defects in general.